Development of an Islamic-Integrated Pancasila Education Learning Module - Sayuti, Ujang; Nurdin, Syafruddin; Kosim, Muhammad; Azhari, Devi Syukri (Journal La Edusci, 2026)
This study aims to develop an Islamic-integrated Pancasila Education learning module for senior high school students at SMAN 1 Gunung Talang, Solok Regency, and to examine its validity, practicality, and effectiveness. The study employed a Research and Development (R&D) approach adapted from established instructional design models, encompassing stages of needs analysis, design, development, expert validation, revision, and limited field testing. Data were collected through observations, interviews, validation questionnaires, response questionnaires, and learning outcome tests. The results of expert validation indicated that the developed module achieved a very high level of validity in terms of content relevance, integration of Islamic values, language clarity, and instructional design. Practicality test results showed positive responses from both teachers and students, indicating that the module is easy to use and suitable for classroom implementation. Furthermore, effectiveness testing revealed a significant improvement in students’ learning outcomes after using the module. These findings suggest that integrating Islamic values into Pancasila Education through a structured learning module can enhance students’ understanding of civic values, moral awareness, and learning motivation. The developed module therefore offers a promising instructional alternative to strengthen character education in senior high schools.